2018 IEEE/ACM 5th International Conference on Big Data Computing Applications and Technologies (BDCAT) 2018
DOI: 10.1109/bdcat.2018.00036
|View full text |Cite
|
Sign up to set email alerts
|

Urban Hourly Water Demand Prediction Using Human Mobility Data

Abstract: The efficient management of a water supply system requires precise water demand forecasts as inputs. This paper compares existing prediction methods and improves their performance by integrating human-related factors with water consumption in an urban area. Furthermore, a framework for processing and transforming mobility data into time-series is presented. Results show that using human mobility data improves forecasting accuracy reaching 87.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Regarding works related to water consumption data and human mobility, Smolak et al [18], [19] compares several ML and statistical models to predict the water usage based on human mobility data. The main aim of this work is the water demand forecasting of a particular area, and they actually concluded that the use of this mobility data is correlated to the water demand and this it benefits its prediction.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding works related to water consumption data and human mobility, Smolak et al [18], [19] compares several ML and statistical models to predict the water usage based on human mobility data. The main aim of this work is the water demand forecasting of a particular area, and they actually concluded that the use of this mobility data is correlated to the water demand and this it benefits its prediction.…”
Section: Related Workmentioning
confidence: 99%
“…The human displacements are defined at a region level in an aggregated form whereas the water consumption data are defined at a much finer granularity as it is extracted directly from smart meters. Although water consumption and human-flow data have already been explored together in several prediction problems [18], [19], it is worth mentioning that their goal was the prediction of the water consumption of a population instead of its movement activity as in our proposal.…”
Section: Introductionmentioning
confidence: 99%